2019
DOI: 10.1016/j.devcel.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Ribosomes Are Sufficient for Tissue Diversification during Embryonic Development in C. elegans

Abstract: Highlights d Functional ribosomes are predominantly maternal during C. elegans embryogenesis d Embryogenesis is complete in the absence of zygotic ribosomal component contributions d Additional ribosome synthesis is needed for postembryonic plasticity of neuronal structure d Ribosomal insufficiency in a subset of cells triggers organism-wide growth arrest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 124 publications
(121 reference statements)
3
39
0
1
Order By: Relevance
“…Protein dynamics is shaped by mRNA and protein half-lives, both of which differ among individual transcripts and proteins but also exhibit a tissue-specific pattern of stability with somewhat higher stability in neuronal tissues (8)(9)(10)(11). A recent study in a genetically well-tractable system, C. elegans (28), and earlier observations in Xenopus embryos (45) suggests that tissue diversification may not rely on ribosomes with a heterogeneous RP pool. Along that line, another study shows that ribosome levels determine the human hematopoietic lineage commitment, while the RP sets remain unchanged (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein dynamics is shaped by mRNA and protein half-lives, both of which differ among individual transcripts and proteins but also exhibit a tissue-specific pattern of stability with somewhat higher stability in neuronal tissues (8)(9)(10)(11). A recent study in a genetically well-tractable system, C. elegans (28), and earlier observations in Xenopus embryos (45) suggests that tissue diversification may not rely on ribosomes with a heterogeneous RP pool. Along that line, another study shows that ribosome levels determine the human hematopoietic lineage commitment, while the RP sets remain unchanged (29).…”
Section: Discussionmentioning
confidence: 99%
“…eL38 or uS2 (22,23), posttranslational modifications (24,25), or detachment of ribosome-associated factors (26) provide examples for tissue-and message-specific expression, prompting the debate on whether a specialized ribosome pool may shape tissue development (27). This argument is challenged by recent observations in C. elegans that tissue diversification is efficiently maintained during embryonic development by maternal ribosomes and synthesis of a new distinct pool of ribosomes is not required (28). The argument for heterogeneous ribosomal pools conferring message-specific expression is used to explain the tissue specificity of haploinsufficiencies associated with germline mutations disrupting one copy of RP genes in a type of ribosomopathies (14,27).…”
Section: Significancementioning
confidence: 99%
“…In either case, however, it would imply that only a subset of translating ribosomes are affected, since the majority of proteins are present at similar levels in both cell lines. Specialised ribosomes have been described in a variety of organisms [59][60][61][62], but have not yet been reported for trypanosomes. Interestingly, Alba4 was mainly present in the free RNA fractions of both AnTat 90-13 and KO cells on day 2, and then shifted progressively to the early polysomes on day 4 and the late polysomes on day 8, implying that its main role is in fully differentiated cells.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Yet it is still unclear how and why a cell would produce such heterogeneity given the complex and energy expensive nature of ribosome biogenesis (Klinge and Woolford, 2019;Peña et al, 2017). Potentially supporting this interpretation, a recent study found that maternal ribosomes are sufficient for embryogenesis in C. elegans (Cenik et al, 2019), meaning that functional ribosome heterogeneity in embryonic cell types must occur after assembly and transport. Such post-synthesis heterogeneity may be selected and functional, but it has also not been ruled out whether natural ribosome deficiency of eS25 is a consequence of aberrant translation events.…”
Section: Discussionmentioning
confidence: 99%